2012
DOI: 10.1111/j.2042-3306.2012.00679.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquired equine polyneuropathy in Norway and Sweden: A clinical and epidemiological study

Abstract: SummaryReasons for performing study: Acquired equine polyneuropathy (AEP, also known as 'Scandinavian knuckling syndrome'), is a serious disease of unknown aetiology, which emerged clustering in horse farms in Sweden, Norway and Finland in the 1990s. Clinical and epidemiological data regarding the syndrome are scarce. Objectives: To describe the clinical and epidemiological findings and outcome in outbreaks of AEP and compare risk factors in affected and unaffected horses on affected farms in Norway and Sweden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 15 publications
(37 reference statements)
3
29
0
Order By: Relevance
“…A second group of presentations in this session covered aspects of neurological conditions, including vertebral osteomyelitis, Sarcocystis neurona and Neospora hughesi . The EVJ supplement included a clinical and epidemiological study describing the novel disease acquired equine polyneuropathy or ‘Scandinavian knuckling syndrome’ . Of unknown aetiology, case clusters of acquired equine polyneuropathy have been reported sporadically since the 1990s.…”
Section: Medicine: Infectious Disease Neurology and Therapeuticsmentioning
confidence: 99%
“…A second group of presentations in this session covered aspects of neurological conditions, including vertebral osteomyelitis, Sarcocystis neurona and Neospora hughesi . The EVJ supplement included a clinical and epidemiological study describing the novel disease acquired equine polyneuropathy or ‘Scandinavian knuckling syndrome’ . Of unknown aetiology, case clusters of acquired equine polyneuropathy have been reported sporadically since the 1990s.…”
Section: Medicine: Infectious Disease Neurology and Therapeuticsmentioning
confidence: 99%
“…Moreover, most affected horses have been fed wrapped forage, suggesting an environmental, possibly feed‐related trigger. Although previous studies concluded that there is no indication of an infectious aetiology, AEP often affects more than only one horse at the farm .…”
Section: Introductionmentioning
confidence: 96%
“…Most recumbent cases are subjected to euthanasia and fatality rates have varied from 29 to 53% . Although horses that remain able to rise up and stand with or without support, seem to recover, one study reported intermittent knuckling up to 17 months after onset of disease . Histopathological examination of peripheral nerves from horses subjected to euthanasia due to AEP has revealed large fibre predominant neuropathy with conspicuous inclusion body schwannopathy and demyelinating inflammation supporting ubiquitous histopathological features.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gr€ ondahl 1 , K Hultin J€ aderlund 2 , S. Hanche-Olsen 2 1 National Veterinary Institute, Uppsala, Sweden; 2 Department of companion animals clinical sciences, Norwegian University of Life Sciences, Oslo, Norway Acquired equine polyneuropathy (AEP) is an emerging disease of horses in northern Europe since the 1990's [1,2]. Gr€ ondahl 1 , K Hultin J€ aderlund 2 , S. Hanche-Olsen 2 1 National Veterinary Institute, Uppsala, Sweden; 2 Department of companion animals clinical sciences, Norwegian University of Life Sciences, Oslo, Norway Acquired equine polyneuropathy (AEP) is an emerging disease of horses in northern Europe since the 1990's [1,2].…”
mentioning
confidence: 99%